QUEIJO MINAS ARTESANAL PRODUZIDO NA REGIÃO DE CANASTRA: CARACTERÍSTICAS DOS PARÂMETROS DE PRODUÇÃO, QUALIDADE DA ÁGUA E DOS QUEIJOS - COURA, F. M.; FERREIRA, F. S.; BARBIERI, J. M.; PACIULLI, S. O. D. (Ars Veterinaria, 2020)
The Serra da Canastra region is known for the production of a characteristic Minas artisanal cheese, named Canastra cheese. The objective of this study was to characterize the microbiological and physicochemical aspects of the water and cheese collected from the Minas artisanal cheese producing properties, as well as to characterize the environmental aspects of cheese manufacturing. The analyzes were carried out by private laboratories and the government in 2016 and 2017 and the results provided were tabulated and analyzed in the present study. In the physical chemical analyses of the water, the highest non-conformity was for free residual chlorine (44.69%). In the microbiological analyses of the water, 17.02% of the samples showed non-conformity for E. coli and total coliform parameters. In the microbiological analyses of the cheese, non-conformities were found in 7.84% of the samples for total coliforms at 30°C and 9.8% for coagulase-positive Staphylococcus spp. The physicochemical analyses of the cheese were all in compliance. No statistical association was found between the quality of the cheese and the water. The water sources were protected, however discard of the waste from cow pens, sanitary sewage, and garbage is still not properly handled. The study indicates that producers need to improve the quality control of the water supply for their cheese factories, fulfill the requirements of chlorine in the water and periodically verify this requirement, ensuring that the produced cheese is safe for human consumption.